2017
DOI: 10.3389/fpls.2017.01032
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Profiling and Identification of Heat-Responsive Genes in Perennial Ryegrass by RNA-Sequencing

Abstract: Perennial ryegrass (Lolium perenne) is one of the most widely used forage and turf grasses in the world due to its desirable agronomic qualities. However, as a cool-season perennial grass species, high temperature is a major factor limiting its performance in warmer and transition regions. In this study, a de novo transcriptome was generated using a cDNA library constructed from perennial ryegrass leaves subjected to short-term heat stress treatment. Then the expression profiling and identification of perennia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 152 publications
3
32
0
Order By: Relevance
“…With respect to the molecular function category, "binding" (19,041 unigenes) and "catalytic activity" (14,935 unigenes) were mostly assigned. Consistent with our results, the aforementioned most highly represented GO terms were also observed in transcriptome analyses of other plant species under heat stress [31,32,43]. Those groups of "nucleic acid binding transcription factor activity" (1097 unigenes), "signaling" (2374 unigenes), "transporter activity" (2468 unigenes), and "response to stimulus" (4699 unigenes) have been implicated in plant stress responses, but with lower numbers of assigned unigenes.…”
Section: Functional Annotation and Classification Of D Involucrata Usupporting
confidence: 87%
See 2 more Smart Citations
“…With respect to the molecular function category, "binding" (19,041 unigenes) and "catalytic activity" (14,935 unigenes) were mostly assigned. Consistent with our results, the aforementioned most highly represented GO terms were also observed in transcriptome analyses of other plant species under heat stress [31,32,43]. Those groups of "nucleic acid binding transcription factor activity" (1097 unigenes), "signaling" (2374 unigenes), "transporter activity" (2468 unigenes), and "response to stimulus" (4699 unigenes) have been implicated in plant stress responses, but with lower numbers of assigned unigenes.…”
Section: Functional Annotation and Classification Of D Involucrata Usupporting
confidence: 87%
“…The comprehensive transcriptomic analysis of Korean fir (Abies koreana) revealed many Hsps and transcription factors as being differentially expressed upon heat treatment [31]. In addition to the previously described heat stress regulators, the transcriptional profiling of perennial ryegrass (Lolium perenne) under heat stress also identified four genes primarily involved in C 4 carbon fixation as well as one target of rapamycin (TOR) gene [32]. In maize (Zea mays), a transcriptome analysis highlights the crucial roles of the protein processing in the endoplasmic reticulum pathway in heat stress response [33].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…According to our results, it was documented that the expression of the HSF_DNA-bind gene was obviously downregulated in the thermotolerant strain S606 after heat stress, which indicated that L. edodes tolerance to heat stress could be negatively controlled by HSF_DNA-bind. Besides, many genes encoding other transcription factors including in bHLH, Myb and C 2 H 2 (Zinc finger family protein) regulated significantly in plant after heat stress [67,68], were among the up-or down-regulated (Table S5). Additionally, the gene expression and protein levels of the BAG gene were dramatically induced and upregulated.…”
Section: Signal Transduction In Response To Heat Stressmentioning
confidence: 99%
“…Clean data were obtained from raw data after removing adapters or poly‐N and other low‐quality reads. Under the criteria of an adjusted P ‐value < 0.05, differentially expressed genes (DEGs) between WT and OE‐miR319 plants were analysed as previously reported (Wang et al ., ). Ten genes were selected to verify their expression levels in the transcriptome by qRT‐PCR using the primers listed in Table S1.…”
Section: Methodsmentioning
confidence: 97%